How do changes in European Union audit committee legal framework impact in earnings management practises? - Monteiro, D.; Pontes, S.; Laureano, Raul M. S. (21st EIASM Workshop on Corporate Governance, 2024)
In the context of the latest (2016) European Union (EU) audit reform related to Public Interest Entities (PIE), we explore the impact of legal framework related to audit committee (AC) member characteristics, independence and expertise, and role in earnings management (EM) practises. Our sample is composed of the first 15 Member States (MS) PIE’s and we measured EM using Ball and Shivakumar and Kothari et al models. The intra-European discrepancies in the ACs’ legal framework before the audit reform provides an excellent opportunity to better understand drivers of EM practises, so we studied both the prior period (2010-2015) when this context was less harmonized, and the period under the current rules (2016-2021). Our findings suggest that the requirement of majority or entirely independent members in ACs does not enhance information quality, as reflected by earnings management. The requirement of members with accounting or auditing expertise also appears to increase earnings management, in contrast to what happens when the role of ACs includes the selection of the external auditor. This evidence suggests that the current framework requires ongoing discussion, and further research in this field should be encouraged. These conclusions might have important implications for regulators and corporate nominating bodies concerning the promotion of AC effectiveness.